A comparative study of the electrorheological properties of various N-doped nanomaterials using ammonia plasma treatment. Issue 26 (10th March 2016) - Yoon, Chang-Min; Lee, Gyeongseop; Noh, Jungchul; Lee, Choonghyeon; Cheong, Oug Jae; Jang, Jyongsik
Abstract : Nanomaterials with different morphologies, sizes, and compositions are successfully treated by ammonia plasma to exhibit significantly enhanced electrorheological (ER) performance. Abstract : A new, simple method is reported to enhance the electrorheological (ER) activity of nanomaterials. Plasma treatment was the ideal technique owing to its ease of use, versatility, and common usage in mass production. Multi-gram quantities of ER nanomaterials with different morphologies, sizes, and compositions were successfully treated by ammonia plasma.